Hypophosphatemia in Critically Ill Children: Insight from a Case Control Study: Hypophosphatemia in Critically Ill Children - Khan, Lubna; Iqbal, Mohammad; Zafar, Farhana; Zaidi, Farah (Pakistan Journal of Health Sciences, 2025)
Hypophosphatemia is a common yet under-recognized electrolyte abnormality in critically ill children. Early detection and treatment of hypophosphatemia can help avoid complications and enhance outcomes in critically ill children. Objectives: To determine the frequency of hypophosphatemia at the time of Pediatric Intensive Care Unit (PICU) admission and throughout the PICU stay, and to evaluate the need for serial phosphate level monitoring. Methods: This case-control study was carried out in the PICU at Ziauddin University Hospital, North Campus, from March to September 2019. Data were collected from 136 (68 cases and 68 controls) patients. At enrollment, each participant underwent a thorough clinical examination. Baseline laboratory investigations were performed according to institutional PICU protocols. Results: On Day 1, 61.7% of cases had hypophosphatemia, rising to 80% by Day 3. Serum phosphate levels were significantly lower in cases than controls at both admission (3.42 ± 1.20 vs. 4.71 ± 0.70 mg/dL) and Day 3 (3.08 ± 0.74 vs. 4.62 ± 0.70 mg/dL), both p<0.001. Cases had a significantly longer duration of illness before admission (10.02 ± 11.99 vs. 5.37 ± 4.74 days; p=0.004) and PICU stay (4.35 ± 2.44 vs. 3.49 ± 1.41 days; p=0.01). Conclusion: It was concluded that hypophosphatemia is common among critically ill children and often develops after admission. A single phosphate measurement at admission is insufficient for detecting all cases. Therefore, a series of phosphate measurements during the PICU stay is recommended.